The poly-orogenic Paleozoic rocks of Cuesta del Rahue area (Precordillera Neuquina, Argentina) and their significance in marking the southern end of the Chanic orogenic belt - Heredia, Nemesio (2023)
In the Cuesta del Rahue area, located in the Precordillera Neuquina (northern Argentine Patagonia), late Paleozoic turbiditic rocks with maximum depositional age of ca. 389 Ma were affected by three orogenic events. The oldest orogenic event is the Chanic orogeny (Late Devonian–early Carboniferous) that is characterized by folds with NNE vergence. This deformation is developed in low-grade to very low-grade metamorphic conditions, which allowed the development of a slaty/rough cleavage. The main Chanic structure is an asymmetric fold with a large normal limb tilted by the more recent orogenic events. The characteristics of the deformation and metamorphism allows us to assign the Cuesta del Rahue outcrop to the external hinterland of the western wedge of the Chanic orogen. Early to late Carboniferous igneous rocks intruded the Paleozoic rocks of the Cuesta del Rahue area and crosscut the Chanic structures. After the Chanic orogeny, the Gondwanan orogeny (late Carboniferous–early Permian) took place. The main structures of the Gondwanan orogen are thrust and related folds with SSW vergence that fold the large Chanic normal limb and also affect Carboniferous igneous rocks. The Gondwanan deformation was developed under non-metamorphic conditions, and Permian igneous rocks crosscut the Gondwanan structures. Mesozoic regional extension related to the beginning of the Andean cycle and the formation of the Neuquén Basin gave rise to normal faults and small-scale extensional folds. Finally, the Andean orogeny, developed during the Cenozoic in the study area, also affected the Cuesta del Rahue Paleozoic rocks, with the development of compressional structures related to the Aluminé thrust and fold belt. The main Andean structure in the study area is the NW–SE Rahue fault, which links the E–W Piedra Santa tear fault with the NNE–SSW Cantan Lil reverse fault. The Rahue fault has a SW tectonic transport direction. It uplifted the Cuesta del Rahue area and placed Paleozoic rocks on top of Mesozoic and Cenozoic rocks. The Piedra Santa fault partially reactivated the Huincul right-lateral and left-lateral Chanic transverse faults that define the southern end of the doubly vergent Chanic orogen, giving rise to the current Huincul lineament.